Narrativas de Jogos de Azar em Plataformas de Vídeo: Um Estudo Linguístico-Temático sobre o jogo do Tigrinho no YouTube - Prenassi, Gabriel; Machado, Ana; Souza, Ester; Brito, Mateus; Reis, Davi; Costa, Jessica; Oliveira, Geovana; Ferreira, Carlos; Rocha, Leonardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15565, 2025)
The dissemination of online gambling, particularly when amplified by digital influencers, presents a growing social concern. In Brazil, the game Fortune Tiger has gained popularity through YouTube videos that often promote quick and effortless earnings. While there is existing research on gambling in social media, our study is among the first to delve into how influencers on video platforms construct and disseminate such narratives. We examine the structure and perception of gambling-related content on YouTube, using a large-scale, linguistically informed thematic analysis. Through transcription, topic modeling, and linguistic feature extraction, we identify two dominant narrative types: critical videos that address legal and social harms, and promotional videos that use simplified and repetitive language to encourage engagement. Promotional content overwhelmingly dominates the platform, while critical content exhibits greater linguistic richness and higher per-video engagement. These findings underscore the structural imbalance in online gambling discourse and offer significant implications for future research, platform moderation, and regulatory frameworks.